Appropriate antibiotics in dog bite injuries: an audit study. Issue 2 (13th October 2020) - Al Omran, Yasser; Evans, Ellie; Jordan, Chloe; Yang, Ding; Huq, Shahidal
Abstract : Background: Dog bite injuries are a common presentation to Accident and Emergency. In the United Kingdom 250, 000 people attend emergency units each year as a result of dog wounds. Currently, there is a lack of consistency in the approach and management of such wounds across plastic surgery units in the United Kingdom. Method: A retrospective review of medical record of patients who were admitted under the care of the Plastic Surgery Department at University Hospital North Midlands NHS Foundation Trust with dog-bite wounds between January and December 2018. Results: Of the 69 patients that were included in the study, 14 (20%) of them had been prescribed antibiotics that were ineffective and against antimicrobial guidelines. Following liaison with the antimicrobial governance team and input from NICE guidelines, the trust's MicroGuide Antibiotic Prescribing Guidelines App was updated. A reaudit from November 2019 to February 2020 showed that there was 100% compliance with guidance. Conclusion: Updating the University Hospital of North Midlands NHS Trust's MicroGuide antibiotic prescribing guidelines for the treatment of dog-bite injuries resulted in 100% of patients being treated with the correct antibiotic. Given the polymicrobial nature of animal-bite wounds, and the high levels of resistance demonstrated by organisms commonly found in such injuries, this increased compliance with guidelines helps minimize patient suffering, morbidity, length of stay, and disability, while reducing costs incurred. The intervention should be implemented within other units within the United Kingdom who similarly lack clear, detailed guidelines, in order to maximize treatment continuity and patient outcomes nationwide.